SenticAPI testing for polarity classification and emotion recognition on Reddit comments regarding ChatGPT - Tan, Mazel Jia Ying (Nanyang Technological University, 2024)
ChatGPT has gained significant popularity across diverse domains, ranging from personal usage to business applications. Despite its widespread popularity, opinions regarding ChatGPT remain varied and at times contradictory. This disparity in perspectives highlights the complexity surrounding understanding ChatGPT's functionality and effectiveness and discerning users' sentiments and attitudes towards ChatGPT remains a challenge due to the diverse range of experiences and use cases. Therefore, it is imperative to delve deeper into understanding the multifaceted perceptions surrounding ChatGPT to ensure informed decisions are made regarding the usage of ChatGPT.